Integrating nitric oxide into salicylic acid and jasmonic acid/ ethylene plant defense pathways - Mur, Luis A.; Prats, Elena; Pierre, Sandra; Hall, Michael A.; Hebelstrup, Kim Henrik (Frontiers in Plant Science, 2013)
Plant defence against pests and pathogens is known to be conferred by either salicylic acid (SA) or jasmonic acid (JA)/ethylene (ET) pathways, depending on infection or herbivore-grazing strategy. It is well attested that SA and JA/ET pathways are mutually antagonistic allowing defence responses to be tailored to particular biotic stresses. Nitric oxide (NO) has emerged as a major signal influencing resistance mediated by both signalling pathways but no attempt has been made to integrate NO into established SA/JA/ET interactions. NO has been shown to act as an inducer or suppressor of signalling along each pathway. NO will initiate SA biosynthesis and nitrosylate key cysteines on TGA-class transcription factors to aid in the initiation of SA—dependent gene expression. Against this, S-nitrosylation of NONEXPRESSOR OF PATHOGENESIS-RELATED PROTEINS1 (NPR1) will promote the NPR1 oligomerisation within the cytoplasm to reduce TGA activation. In JA biosynthesis, NO will initiate the expression of JA biosynthetic enzymes, presumably to over-come any antagonistic effects of SA on JA-mediated transcription. NO will also initiate the expression of ET biosynthetic genes but a suppressive role is also observed in the S –nitrosylation and inhibition of s-adenosylmethionine transferases which provides methyl groups for ethylene production. Based on these data a model for NO action is proposed but we have also highlighted the need to understand when and how inductive and suppressive steps are used.